2015
DOI: 10.1179/0032589915z.000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subsequent Hot Isostatic Pressing on mechanical properties of ASTM F75 alloy produced by Selective Laser Melting

Abstract: The Co-based alloy ASTM (Co -28.5 wt.-% Cr -6.3 wt.-% Mo) is widely used for medical implants, e.g. knee prostheses, and is commonly processed by investment casting. Selective laser (SLM) melting is supposed to be an efficient alternative for the production of individually designed knee implants regarding production time and production costs. The mechanical properties, in particular the fatigue strength, of the material have been studied in different states of the material. The mechanical properties of investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 11 publications
6
24
0
4
Order By: Relevance
“…This significant increase in the ultimate tensile strength of the water‐atomized L‐PBF parts after the HIP treatment could be attributed to the increase in density of L‐PBF parts (3%‐6%; Figure ). This relation between the ultimate tensile strength and the porosity of the L‐PBF parts after the HIP treatment was observed in previous studies …”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This significant increase in the ultimate tensile strength of the water‐atomized L‐PBF parts after the HIP treatment could be attributed to the increase in density of L‐PBF parts (3%‐6%; Figure ). This relation between the ultimate tensile strength and the porosity of the L‐PBF parts after the HIP treatment was observed in previous studies …”
Section: Resultssupporting
confidence: 85%
“…Metallographic specimen preparation was carried out following standard procedures for microstructure characterization. The carpenter's etchant was used as an etchant to reveal the austenite and martensitic phases typically found 17‐4PH stainless steel parts . The tensile testing of the L‐PBF parts and microstructural characterization of the polished and etched L‐PBF parts were performed in the horizontal plane perpendicular to the build direction.=…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For D2 powder particle because of its smaller specific surface area, it obtained the highest result of beat density (equal to 5.26 g/cm 3 ). According to Haan et al [19], powder flow time and apparent density of the alloy Co-Cr-Mo study showed relevant results to those obtained respectively for powders with D90 diameter equal to 39 µm, the flow time was 18.60 s/cm 3 and bulk density was 4.38 g/cm 3 .…”
Section: Feedstock Materialsmentioning
confidence: 82%